Reaction Time Effect: For Foot Agility in Takraw Athletes - Yongki Faradila; Yolanda Kristiani Sitepu; Yonathan Alexander Barus (Joska: Jurnal Isori Kampar, 2024)
Objectives: Sepak takraw is a traditional Southeast Asian sport requiring exceptional foot agility, rapid decision-making, and precise motor control. Reaction time plays a crucial role in athletic performance, particularly in sports demanding quick foot movements and ball control. However, limited research has examined the specific relationship between reaction time and foot agility performance in takraw athletes. This study aimed to investigate the correlation between reaction time and foot agility performance in sepak takraw athletes, and to determine whether reaction time training could enhance foot agility skills in this population. Methods: Twenty-eight male sepak takraw athletes (age: 22.4 ± 3.2 years) from a takraw club in Deli Serdang, North Sumatra, participated in this cross-sectional study. Participants underwent reaction time assessment using computerized testing and foot agility evaluation through standardized takraw-specific agility tests. Pearson correlation analysis and multiple regression were performed using SPSS v27. Results: Significant negative correlations were found between reaction time and foot agility performance (r = -0.742, p < 0.001). Athletes with faster reaction times (≤ 250ms) demonstrated superior foot agility scores (18.4 ± 2.1) compared to those with slower reaction times (> 300ms) (14.2 ± 2.8, p < 0.001). Reaction time explained 55.1% of the variance in foot agility performance. Conclusion: Reaction time significantly influences foot agility performance in sepak takraw athletes. These findings suggest that incorporating reaction time training into sepak takraw training programs may enhance athletic performance and foot agility skills.